2019
DOI: 10.1109/access.2019.2924335
|View full text |Cite
|
Sign up to set email alerts
|

User Generated Information on Mobile Channels With More Concise Reviews and More Extreme Ratings

Abstract: Online word of mouth is shifting from personal computer (PC)-based channels to mobile-based channels in this mobile marketing age, which leads to the question of whether mobile word of mouth is shorter and louder than the PC word of mouth? By investigating the 162 452 pieces of online word of mouth created by 19 496 users on a top-three online shopping website in China during a two-year period, this paper successfully discovered that mobile reviews are shorter than PC reviews and that mobile ratings are more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Yet, information about the device used is neglected on many platforms. Given the influence of submission devices on the textual features of a review and the wide adoption of smartphones, providing device information could help viewers in terms of using online reviews (März et al, 2017;Jia and Wu, 2019;Ransbotham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, information about the device used is neglected on many platforms. Given the influence of submission devices on the textual features of a review and the wide adoption of smartphones, providing device information could help viewers in terms of using online reviews (März et al, 2017;Jia and Wu, 2019;Ransbotham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One potential source of the associations is differences between mobile and non-mobile reviews. Researchers have indicated that depending on whether they are posted from a mobile or non-mobile device, reviews differ in terms of textual features such as length, valence, and word use (März et al, 2017;Jia and Wu, 2019;Ransbotham et al, 2019). Although there are some inconsistencies across the findings presented in previous studies depending on the platforms and the study periods, one consistent finding across several studies is that mobile reviews as compared with nonmobile reviews are shorter in length (Piccoli and Ott, 2014;Jia and Wu, 2019;Mariani et al, 2019;Zhu et al, 2020).…”
Section: Review Of Literature and Hypotheses Mobile Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mokhlis and Yaakop [ 23 ], who studied Malaysian university students, found that the three most important criteria influencing smartphone choice behavior were innovative product features, price, and word of mouth. Similar studies recommended word-of-mouth (social influence) for consideration in promoting smartphones among university students [ 24 , 25 ]. In the same vein [ 26 ], concluded that peer influence, self-innovativeness, self-efficacy, attitude, budget, age, and gender were significant factors that influenced demand for smartphone purchase by Malaysian consumers.…”
Section: Literature Reviewmentioning
confidence: 99%